Particulate matter emission and K/S/Cl transformation during biomass combustion in an entrained flow reactor. Issue 6 (December 2018) - Wang, Xuebin; Hu, Zhongfa; Adeosun, Adewale; Liu, Bin; Ruan, Renhui; Li, Shuaishuai; Tan, Houzhang
Abstract: This study aims to demonstrate the effect of ash chemistry, especially, the transformation of potassium (K), chlorine (Cl), and sulfur (S) species, on the fine particle emission during biomass combustion. Biomass was burned in an entrained flow reactor at varied temperature from 1000 to 1300 °C, where fine particles were sampled using a 13-stage low pressure impactor, and the morphology and composition of the fine particles were analyzed. The fates of K, Cl, and S during biomass combustion were compared between the entrained flow reactor and the muffle furnace. Results show that the particle size distributions of PM10 are bimodal for all studied cases. A higher concentration of fine-mode particle is observed at 1000 °C, with the peak position at 0.274 μm. When the temperature is increased from 1000 to 1100 °C or higher, the concentration of fine-mode particle is reduced by about 50%, and its size becomes smaller with a peak position at 0.097 μm. K, Cl and S are enriched as potassium chloride and sulfate, dominantly in PM1.0 ; while Mg, Ca and Si are enriched in PM1.0–10 . A certain amount of sulfur in PM1.0 at 1000 °C is observed, while the sulfur disappears above 1100 °C. This indicates that the process of potassium sulfation tends to occur at a moderate temperature, and affects the emission amount and the particle size distribution of particulate matters. Analyzing results of the fates of K, Cl and S in the particle phase indicate a completed sulfur-release from biomass ash above 1200 °C, as well as a maximum capture efficiency for potassium-containing vapors at 1100 °C, which results in a minimum PM1.0 emission at 1100 °C. Highlights: Fine particle formation during biomass combustion is studied at high temperatures. Enhanced sulfation at 1000 °C results in a significant shift in the PSD of PM1.0 . Minimum PM1.0 emission a nd maximum K retaining in ash are observed at 1100 °C. A complete sulfur-release is observed above 1200 °C.